High-voltage solid-state lithium battery and preparation method thereof
By preparing the composite of BaTiO3-LLZO composite material with polymer and lithium salt, a composite solid electrolyte is formed, which solves the shortcomings of the existing composite solid electrolyte in lithium ion conductivity and high-voltage resistance, and achieves the improvement of lithium-ion batteries in terms of energy density, cycle life and safety.
Patent Information
- Application Number
- CN202411954317.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing composite solid electrolytes have shortcomings in lithium ion conductivity and high-voltage resistance, which is difficult to meet the needs of lithium ion batteries to improve energy density, cycle life and safety.
By preparing the composite material of BaTiO3-LLZO with polymer and lithium salt, a composite solid electrolyte is formed, the lithium ion conductivity is improved, and the stability of the electrochemical window is expanded.
The lithium ion conductivity is improved, the electrochemical window is expanded to 4.9V, and the mechanical properties and electrochemical stability of the battery are enhanced.
Smart Images

Figure CN119786747A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and in particular to a high-voltage solid-state lithium battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries play a huge role in promoting social development, and their application areas include consumer electronics, power batteries, etc. However, the current commercial batteries can no longer meet the needs of the rapid development of society. Now the development of batteries needs to have higher energy density, longer cycle life, and be safer and cheaper. Traditional liquid lithium-ion batteries have high conductivity and excellent electrode surface wettability, but their electrochemical performance and thermal stability are poor, and their ion selectivity is low. They face many risks such as short circuit, flammability, leakage and explosion. Using solid electrolytes to replace traditional liquid electrolytes is an effective way to control and solve the above problems. Compared with liquid electrolytes, solid electrolytes have the advantages of high safety, wide electrochemical window and high energy density. Solid electrolytes are mainly divided into inorganic solid electrolytes, organic solid electrolytes and composite solid electrolytes according to their composition. Inorganic solid electrolytes have significant advantages in safety, electrochemical stability and ionic conductivity, but they still face challenges in terms of interface impedance, cost and thermal stability. Organic solid electrolytes are mainly composed of an organic polymer matrix and lithium salts or sodium salts. They have the advantages of good flexibility, easy processing and molding, and good electrode interface compatibility. However, they have problems such as low room temperature ionic conductivity and poor mechanical strength, making them difficult to use alone. Composite solid electrolytes are generally prepared by combining inorganic solid electrolytes and organic solid electrolytes. They have the excellent properties of both inorganic and organic solid electrolytes, good interface compatibility, high ionic conductivity, and excellent electrochemical stability. They are currently one of the important materials to replace liquid electrolytes. However, existing composite solid electrolytes still face the problems of low lithium ion conductivity and limited high voltage resistance. Summary of the invention
[0003] In view of the problems existing in the background technology, the purpose of the present invention is to provide a method for preparing a composite solid electrolyte and its application, by preparing a BaT iO3-LLZO composite material and compounding it with a polymer and a lithium salt, so as to improve the lithium ion conductivity of the solid electrolyte and improve the stability of its electrochemical window.
[0004] In order to achieve the above objectives, the present application proposes the following technical solutions:
[0005] A method for preparing a high-voltage solid-state lithium battery, characterized in that it comprises a positive electrode, a negative electrode and a solid electrolyte, wherein the positive electrode active material is a ternary material of lithium nickel cobalt manganese oxide, and the solid electrolyte comprises a polymer, a BaTiO3 / LLZO composite material and a lithium salt, wherein the preparation steps of the solid electrolyte are as follows:
[0006] Step 1: Weigh a titanium source, a barium source and urea in a molar ratio of 1:1:(2-3), dissolve in 80-100 mL of ethanol, and stir evenly;
[0007] Step 2: adding hexadecyltrimethylammonium chloride to the solution obtained in step 1, stirring evenly to obtain a precursor mixed solution;
[0008] Step 3: transfer the precursor mixture of step 2 to a polytetrafluoroethylene reactor, heat it with microwave, control the temperature at 200-250°C, and react for 20-60 minutes; after the reaction, filter it, wash it with deionized water, and dry it to obtain BaTiO3;
[0009] Step 4: Weigh a certain molar ratio of lithium salt, lanthanum salt and zirconium salt, dissolve them in deionized water and stir evenly; continue to add chelating agent and polyethylene glycol PEG2000, stir evenly, then add BaTiO3 prepared in step 3, continue to stir evenly, place in an oven at 60-70°C to evaporate the solvent to obtain a gel, and calcine at 600-900°C for 2-3h to obtain a BaTiO3-LLZO composite material;
[0010] Step 5: Dissolve the BaTiO3-LLZO composite material, polymer and lithium salt in an organic solvent, stir and mix evenly, and dry to obtain a solid electrolyte.
[0011] Furthermore, the lithium source is one or more of lithium nitrate and lithium hydroxide.
[0012] Furthermore, the lanthanum source is one or more of lanthanum nitrate and lanthanum oxide.
[0013] Furthermore, the zirconium source is zirconium nitrate.
[0014] Furthermore, the molar ratio of the lithium source, lanthanum source and zirconium source is (7-7.1):3:2.
[0015] Furthermore, the BaTiO3-LLZO material is a nanosheet structure of LLZO generated on the surface of BaTiO3 nanorods.
[0016] Furthermore, the chelating agent is citric acid or tartaric acid.
[0017] Furthermore, the mass ratio of the inorganic material, polymer and lithium salt of BaTiO3-LLZO is (1-3):(5-7):(1-2);
[0018] Further, the polymer is PEO or PVDF;
[0019] Furthermore, the amount of polyethylene glycol PEG200 added is 1-5 g;
[0020] Further, the amount of hexadecyltrimethylammonium chloride added is 2-5 g;
[0021] By adopting the above technical solution, the present invention can achieve the following technical effects:
[0022] The present application uses BaT iO3-LLZO to composite with polymers and lithium salts to form a composite solid electrolyte. The BaT iO3-LLZO material is a nanosheet structure of LLZO generated on the surface of BaT iO3 nanorods with a high aspect ratio. On the one hand, this structure can serve as a rigid skeleton to improve the mechanical properties of the composite solid electrolyte and form a high-speed lithium ion shuttle network to effectively improve the lithium ion conductivity; on the other hand, the composite solid electrolyte can increase the operating voltage range of the battery and expand the electrochemical window to 4.9V. In addition, LLZO itself has excellent lithium ion conductivity, and its combination with BaT iO3 nanorods is beneficial to further improve the ion conduction rate of the composite solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the SEM image of the BaT iO3-LLZO composite material of the present application. DETAILED DESCRIPTION
[0024] The present invention is further illustrated below through the description of specific implementation modes, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of the present invention, but as long as they do not deviate from the basic idea of the present invention, they are all within the scope of the present invention.
[0025] Example 1
[0026] Step 1: Weigh tetrabutyl titanate, barium nitrate and urea in a molar ratio of 1:1:2, dissolve in 85 mL of ethanol, wherein tetrabutyl titanate is 3.4 g, barium nitrate is 2.6 g, and urea is 1.2 g, and stir evenly;
[0027] Step 2: Add 3.2 g of hexadecyltrimethylammonium chloride to the solution obtained in step 1, stir evenly, and obtain a precursor mixed solution;
[0028] Step 3: transfer the precursor mixture of step 2 to a polytetrafluoroethylene reactor, heat with microwave, control the temperature at 200°C, and react for 30 minutes; after the reaction, filter, wash with deionized water, and dry to obtain BaTiO3;
[0029] Step 4: Weigh 4.76g of lithium nitrate, 9.72g of lanthanum nitrate, and 27.6g of zirconium acetate and dissolve them in 40mL of deionized water, and stir evenly; continue to add chelating agent citric acid and 4g of polyethylene glycol PEG2000, stir evenly, then add BaTiO3 prepared in step 3, stir evenly, place in an oven at 60°C to evaporate the solvent, obtain a gel, and calcine at 800°C for 2h to obtain an inorganic composite material of BaTiO3-LLZO;
[0030] Step 5: Dissolve 0.2 g of BaT iO3-LLZO inorganic composite material, 0.6 g of polymer PVDF and 0.2 g of lithium hexafluorophosphate in 10 mL of organic solvent DMF, stir and mix evenly, and dry to obtain a solid electrolyte.
[0031] Example 2
[0032] Step 1: Weigh tetrabutyl titanate, barium nitrate and urea in a molar ratio of 1:1:2, dissolve in 85 mL of ethanol, wherein tetrabutyl titanate is 3.4 g, barium nitrate is 2.6 g, and urea is 1.2 g, and stir evenly;
[0033] Step 2: Add 2.1 g of hexadecyltrimethylammonium chloride to the solution obtained in step (1), stir evenly, and obtain a precursor mixed solution;
[0034] Step 3: transfer the mixed solution of step 2 to a polytetrafluoroethylene reactor, heat it with microwave, control the temperature at 200°C, and react for 30 minutes; after the reaction, filter it, wash it with deionized water, and dry it to obtain BaTiO3;
[0035] Step 4: Weigh 2.38g of lithium nitrate, 4.86g of lanthanum nitrate, and 13.3g of zirconium acetate and dissolve them in 40mL of deionized water, and stir evenly; continue to add chelating agent tartaric acid and 2g of polyethylene glycol PEG2000, stir evenly, then add BaTiO3 prepared in step 3, stir evenly, place in an oven at 60°C to evaporate the solvent, obtain a gel, and calcine at 800°C for 2h to obtain an inorganic composite material of BaTiO3-LLZO;
[0036] Step 5: Dissolve 0.2g of BaT iO3-LLZO inorganic composite material, 0.6g of polymer PVDF and 0.2g of lithium hexafluorophosphate in 10mL of organic solvent DMF, stir and mix evenly, and dry to obtain a solid electrolyte.
[0037] Example 3
[0038] Step 1: Weigh tetrabutyl titanate, barium nitrate and urea in a molar ratio of 1:1:2, dissolve in 85 mL of ethanol, wherein tetrabutyl titanate is 3.4 g, barium nitrate is 2.6 g, and urea is 1.2 g, and stir evenly;
[0039] Step 2: Add 3.2 g of hexadecyltrimethylammonium chloride to the solution obtained in step (1), stir evenly, and obtain a precursor mixed solution;
[0040] Step 3: transfer the mixed solution of step 2 to a polytetrafluoroethylene reactor, heat it with microwave, control the temperature at 230°C, and react for 25 minutes; after the reaction, filter it, wash it with deionized water, and dry it to obtain BaTiO3;
[0041] Step 4: Weigh 2.38 g of lithium nitrate, 4.86 g of lanthanum nitrate, and 13.3 g of zirconium acetate and dissolve them in 40 mL of deionized water, and stir evenly; continue to add chelating agent citric acid and 2 g of polyethylene glycol PEG2000, stir evenly, then add BaT iO3 prepared in step 3, continue to stir evenly, place in an oven at 60 ° C to evaporate the solvent, obtain a gel, and calcine at 900 ° C for 2 hours to obtain an inorganic composite material of BaT iO3-LLZO;
[0042] Step 5: Dissolve 0.2g of BaT iO3-LLZO inorganic composite material, 0.6g of polymer PVDF and 0.2g of lithium hexafluorophosphate in 10mL of organic solvent DMF, stir and mix evenly, and dry to obtain a solid electrolyte.
[0043] Example 4
[0044] Step 1: Weigh tetrabutyl titanate, barium nitrate and urea in a molar ratio of 1:1:3, dissolve in 85 mL of ethanol, wherein tetrabutyl titanate is 3.4 g, barium nitrate is 2.6 g, and urea is 1.3 g, and stir evenly;
[0045] Step 2: Add 3.2 g of hexadecyltrimethylammonium chloride to the solution obtained in step 1, stir evenly, and obtain a precursor mixed solution;
[0046] Step 3: transfer the mixed solution of step 2 to a polytetrafluoroethylene reactor, heat it with microwave, control the temperature at 230°C, and react for 25 minutes; after the reaction, filter it, wash it with deionized water, and dry it to obtain BaTiO3;
[0047] Step 4: Weigh 2.38 g of lithium nitrate, 4.86 g of lanthanum nitrate, and 13.3 g of zirconium acetate and dissolve them in 40 mL of deionized water, and stir evenly; continue to add chelating agent citric acid and 2 g of polyethylene glycol PEG2000, stir evenly, then add BaT iO3 prepared in step 3, continue to stir evenly, place in an oven at 60 ° C to evaporate the solvent, obtain a gel, and calcine at 900 ° C for 2 hours to obtain an inorganic composite material of BaT iO3-LLZO;
[0048] Step 5: Dissolve 0.2g of BaT iO3-LLZO inorganic composite material, 0.6g of polymer PVDF and 0.2g of lithium hexafluorophosphate in 10mL of organic solvent DMF, stir and mix evenly, and dry to obtain a solid electrolyte.
[0049] Comparative Example 1
[0050] Step 1: Weigh tetrabutyl titanate, barium nitrate and urea in a molar ratio of 1:1:2, dissolve in 85 mL of ethanol, wherein tetrabutyl titanate is 3.4 g, barium nitrate is 2.6 g, and urea is 1.2 g, and stir evenly;
[0051] Step 2: Add 3.2 g of hexadecyltrimethylammonium chloride to the solution obtained in step 1, stir evenly, and obtain a precursor mixed solution;
[0052] Step 3: transfer the mixed solution of step 2 to a polytetrafluoroethylene reactor, heat it with microwave, control the temperature at 200°C, and react for 30 minutes; after the reaction, filter it, wash it with deionized water, and dry it to obtain BaTiO3;
[0053] Step 4: Dissolve 0.2g of BaT iO3 inorganic material, 0.6g of polymer PVDF and 0.2g of lithium hexafluorophosphate in an organic solvent, stir and mix evenly, and dry to obtain a solid electrolyte.
[0054] Comparative Example 2
[0055] Step 1: Weigh 4.76 g of lithium nitrate, 9.72 g of lanthanum nitrate, and 27.6 g of zirconium acetate, dissolve in 40 mL of deionized water, and stir evenly; continue to add chelating agent citric acid and 4 g of polyethylene glycol PEG2000, mix evenly, place in an oven at 60°C to evaporate the solvent to obtain a gel, and calcine at 800°C for 2 hours to obtain an inorganic material of LLZO;
[0056] Step 2: Dissolve 0.2g of LLZO inorganic composite material, 0.6g of polymer PVDF and 0.2g of lithium hexafluorophosphate in an organic solvent, stir and mix evenly, and dry to obtain a solid electrolyte.
[0057] Comparative Example 3
[0058] The difference between it and Comparative Example 1 is that the BaTiO3-LLZO composite material is not added to the solid electrolyte.
[0059] Test Case
[0060] Select LiNi 0.8 Co 0.1 Mn 0.1O2 is the positive electrode active material, the metal lithium sheet is the negative electrode, the solid electrolyte thickness of Examples 1-4 and Comparative Examples 1-3 is 50 microns, and they are assembled into batteries and subjected to performance tests. The results are shown in Table 1 below.
[0061] Table 1: Test results
[0062]
[0063] As can be seen from the above figure, after the PVDF polymer is modified by BaTiO3-LLZO composite material, its voltage window is further improved compared with pure PVDF and PVDF modified by BaTiO3 and LLZO respectively, and the ionic conductivity, the first reversible capacity of the battery and the cycle efficiency are all improved. This fully demonstrates that BaTiO3-LLZO can effectively improve the ionic conductivity and electrochemical stability of the solid electrolyte.
[0064] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a high-voltage solid-state lithium battery, characterized in that: It includes a positive electrode, a negative electrode and a solid electrolyte, wherein the positive electrode active material is a nickel cobalt lithium manganese oxide ternary material, and the solid electrolyte includes a polymer, a BaTiO3 / LLZO composite material and a lithium salt, wherein the preparation steps of the solid electrolyte are as follows: Step 1: Weigh a titanium source, a barium source and urea in a molar ratio of 1:1:(2-3), dissolve in 80-100 mL of ethanol, and stir evenly; Step 2: adding hexadecyltrimethylammonium chloride to the solution obtained in step 1, stirring evenly to obtain a precursor mixed solution; Step 3: transfer the precursor mixture of step 2 to a polytetrafluoroethylene reactor, heat it with microwave, control the temperature at 200-250°C, and react for 20-60 minutes; after the reaction, filter it, wash it with deionized water, and dry it to obtain BaTiO3; Step 4: Weigh lithium source, lanthanum source and zirconium source, dissolve them in deionized water and stir evenly; continue to add chelating agent and polyethylene glycol PEG2000, stir evenly, then add BaTiO3 prepared in step 3, stir evenly, place in an oven at 60-70°C to evaporate the solvent to obtain a gel, and calcine at 600-900°C for 2-3h to obtain an inorganic composite material of BaTiO3-LLZO; Step 5: Dissolve the BaTiO3-LLZO composite material, polymer and lithium salt in an organic solvent, stir and mix them evenly, and dry to remove the solvent to obtain a solid electrolyte.
2. According to the method for preparing a high-voltage solid-state lithium battery according to claim 1, the lithium source is lithium nitrate or lithium hydroxide.
3. According to the method for preparing a high-voltage solid-state lithium battery according to claim 1, the lanthanum source is lanthanum nitrate or lanthanum oxide.
4. The method for preparing a high-voltage solid-state lithium battery according to claim 1, wherein the zirconium source is zirconium nitrate.
5. According to the method for preparing a high-voltage solid-state lithium battery according to claim 1, the molar ratio of the lithium source, lanthanum source and zirconium source is (7-7.1):3:
2.
6. According to the method for preparing a high-voltage solid-state lithium battery according to claim 1, the BaTiO3-LLZO material is a nanosheet structure in which LLZO is generated on the surface of BaTiO3 nanorods.
7. The method for preparing a high-voltage solid-state lithium battery according to claim 1, wherein the chelating agent is citric acid or tartaric acid.
8. According to the method for preparing a high-voltage solid-state lithium battery as described in claim 1, the titanium source is one or more of tetrabutyl titanate, fluorotitanic acid, and titanium tetrachloride; the barium source is one or more of barium chloride, barium hydroxide, barium acetate, and barium nitrate.
9. The method for preparing a high-voltage solid-state lithium battery according to claim 1, wherein the polymer is PVDF or PEO.
10. A high voltage solid-state lithium battery, characterized in that: Prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of composite solid electrolyte film for energy storage charging system battery
CN112599845A
Solid-state composite polymer electrolyte, electrolyte membrane preparation method and lithium ion battery
CN115472905A
A negative electrode and manufacturing method thereof
KR1020250059325A
Composition For Polymer Electrolyte And Lithium Secondary Battery Including The Same
US20190115616A1
Cited By
Active and inert filler synergistically reinforced composite solid electrolyte and preparation method thereof
CN122051342A